The Meaning of Muhammadiyah Organizational Communication Networks in the Film Buya Hamka Vol. 1: Roland Barthes' Semiotic Analysis of the Representation of Leadership and Da'wah Authority - Muhammad Randicha Hamandia; Anang Anas Azhar (Fakultas Ushuluddin Adab dan Dakwah UIN Sultanah Nahrasiyah Lhokseumawe, 2026)
The film Buya Hamka Vol. 1 (2023) is a cultural artifact that visually represents the dynamics of Islamic broadcasting and the manifestation of print communication technology in early 20th-century Indonesia. This study aims to examine the meaning of the Muhammadiyah organizational communication network, the representation of leadership, and the da'wah authority of Buya Hamka using Roland Barthes' semiotic analysis approach. By dissecting the signification of denotation, connotation, and myth in key scenes and dialogues, this research reveals that the Muhammadiyah organizational communication network did not operate in a vacuum, but was closely intertwined with political communication strategies under the pressure of colonial regimes and the Japanese occupation. The analysis results show: (1) Denotatively and connotatively, Hamka's leadership is represented through the utilization of the Pedoman Masyarakat magazine as an instrument of